125I Radiotherapy combined with metronomic chemotherapy may boost the abscopal effect, leading to complete regression of liver metastasis in an SCLC patient with a 58.5-month OS: a case report - Lu, Linlin; Wang, Yu; Li, Lei; Yu, Lan; Liu, Li; Qu, Baozhen; Zhang, Xiaotao (Frontiers in Oncology, 2023)
The liver is the most common and lethal metastatic site in patients with extensive-stage small-cell lung cancer (ES-SCLC), and median survival with current standard treatment is only 9–10 months from diagnosis. Clinical observations show that a complete response (CR) is extremely rare in ES-SCLC patients with liver metastasis. Moreover, to the best of our knowledge, complete regression of liver metastasis induced by the abscopal effect, boosted primarily by permanent radioactive iodine-125 seeds implantation (PRISI), combined with a low-dose metronomic temozolomide (TMZ) regimen, has not been recorded. Here, we present the case of a 54-year-old male patient who developed multiple liver metastases from ES-SCLC after multiple lines of chemotherapy. The patient was given partial PRISI therapy (two out of six tumor lesions; 38 iodine-125 seeds in one dorsal lesion and 26 seeds in one ventral lesion), which was combined with TMZ metronomic chemotherapy (50 mg/m2/day, days 1–21, every 28 days). The abscopal effect was observed for 1 month after PRISI treatment. After about 1 year, all the liver metastases had completely disappeared, and the patient experienced no relapse. The patient eventually died of malnutrition caused by a non-tumor intestinal obstruction and had an overall survival of 58.5 months after diagnosis. PRISI combined with TMZ metronomic chemotherapy might be considered a potential therapy to trigger the abscopal effect in patients with liver metastases.